Insani, S U Upaya Meningkatkan Kemampuan Pemecahan Masalah Matematika Siswa Melalui Problem Based Learning pada Siswa Kelas VIII SMP Negeri 37 Pekanbaru - Sri Ulfa Insani; Sity Rahmy Maulidya (Jurnal Pustaka Cendekia Pendidikan, 2026)
This research was motivated by the low mathematical problem-solving ability of eighth-grade students at SMP Negeri 37 Pekanbaru. One of the efforts that can be made to improve this ability is by implementing the Problem Based Learning (PBL) model. This study aimed to improve students’ mathematical problem-solving ability through the implementation of the Problem Based Learning model in class VIII.2 of SMP Negeri 37 Pekanbaru. This research was a Classroom Action Research (CAR) conducted in two cycles. Each cycle consisted of four stages: planning, action implementation, observation, and reflection. The subjects of this study were 39 students of class VIII.2 at SMP Negeri 37 Pekanbaru. Data were collected through mathematical problem-solving ability tests, observation sheets of teacher and student activities, and documentation. The data were analyzed using descriptive quantitative and qualitative methods. The results showed that the implementation of the Problem Based Learning model was able to improve students’ mathematical problem-solving ability. This can be seen from the increase in the average score of students’ mathematical problem-solving tests, from 76.8 in the pre-cycle to 82.4 in Cycle I, and further increased to 85.7 in Cycle II. In addition, students’ learning activities also improved, as indicated by their active participation in identifying problems, engaging in group discussions, expressing opinions, and developing solutions to the given problems. Based on the results of the study, it can be concluded that the implementation of the Problem Based Learning model can improve the mathematical problem-solving ability of eighth-grade students at SMP Negeri 37 Pekanbaru. Therefore, this model can be used as an alternative approach in mathematics learning to enhance students’ problem-solving abilities.